(untitled) (Docentes 2.0 Journal, 2024)
Self-efficacy in higher education teachers is a fundamental factor influencing their and students’ academic performance. The objective of this research was to evaluate the self-efficacy of teachers and the possible relationship it has with the training of pedagogical, disciplinary, and technological knowledge they have received. It was based on a comparative method, positivist paradigm, with a quantitative approach, non-experimental design, hypothetical-deductive method, statistical type, and cross-section. One hundred nine teachers from various academic areas of the TecNM Hermosillo campus participated, and they have ten engineering degrees in addition to 1 bachelor’s degree. The instrument had 90 items with a total reliability of .95 on a Likert scale, with dimensions and indicators of the TPACK model. The analysis of variance indicated that older teachers have less technological knowledge than their pedagogical and disciplinary knowledge. In addition, teachers from the Basic Sciences department showed a lower level of knowledge about ICT use than the Metalworking department, who taught 13 to 20 hours and had greater knowledge. It was concluded that the differences in the use and frequency of technologies in the classroom are related to the process of teacher self-efficacy.